Ethical Leadership and Employee Performance: A Systematic Literature Review of HRM Perspectives - Pasagi, Yunior; Hidayat, Muhammad (Penelitian dan Pengembangan Ilmu, 2024)
Ethical leadership plays a key role in improving employee performance by promoting integrity, transparency, and fairness in the organization. This research aims to explore the relationship between ethical leadership and employee performance in various industries using a systematic literature review (SLR) approach. The PRISMA method was used to identify, select, and synthesize relevant articles from leading international databases. The results of the analysis show that ethical leadership is consistently positively related to employee performance through mediation such as employee involvement and organizational citizenship behavior. This research suggests that implementing ethical leadership tailored to industrial contexts can increase employee engagement and productivity, and suggests longitudinal studies and further research to understand the long-term and contextual effects of ethical leadership.